Eficiencia de la cirugia mayor ambulatoria y hospitalaria en artroscopia de rodilla - Vargas Morales, Renán Estuardo (2009)
Introduction: The meniscus and ligament knee pathology is common and the most require arthroscopic treatment. The health management is interested in optimize resources and improve the care quality. Objective: To determine the outpatient surgery and hospital efficiency in knee arthroscopy. Material and methods: A quasi-experimental research, during the period September 2007 - December 2008. It is based in the efficiency of knee inpatient and outpatient arthroscopy in the Traumatology Service of the Victor Lazarte Echegaray Hospital. The investigation considered 36 patients in each group, over 18 years of age. Results: The morbidity is low, the patient functionality and satisfaction is good and very good, respectively. These aspects are not statistically significant. However, the cost of outpatient arthroscopy allows a 34,5% saving compared to the hospital one. The saving achieved is an important factor to recommend it’s frequently use. Conclusions: The outpatient surgery is more efficient than the hospital for knee arthroscopy.